Physical Education for a Sustainable Future: Merging Promotion of Health Through Physical Literacy With Global Environmental Responsibility - Schnitzler, Christophe; Royet, Thomas; Derigny, Thibaut; Cece, Valerian (Australian journal of environmental education, 2025)
This article examines how redefining health through the perspectives of One Health, EcoHealth and Planetary Health can enrich Physical Education (PE) by advancing both health and environmental sustainability. While PE and health education are often treated as separate subjects, most PE curricula worldwide emphasise the promotion of an active lifestyle as a key component of health education through PE. This promotion of an active lifestyle is central to the concept of physical literacy (PL), which is a fundamental aspect of quality PE according to UNESCO (2015). This article focuses on how PE, contributing to health education through the promotion of PL, can evolve to incorporate sustainability goals through the recent new definitions of approaches to health. One Health approach underscores the interconnections between human, animal and environmental health, expanding PL to address zoonotic diseases and ecological impacts. EcoHealth highlights the sustainability of ecosystems, promoting PE activities that (re)connect humans with the more-than-human worlds without causing environmental harm. Planetary Health takes a global perspective, encouraging sustainable physical activities that reduce ecological footprints, such as cycling and walking. By integrating these holistic frameworks, PE can nurture not only individual health outcomes but also environmental stewardship and global health awareness. This shift seeks to educate individuals about their PL, but also their responsibility in preserving ecosystems and the planet, fostering a more sustainable and environmentally aware generation through PE.